Drug Repositioning for the Prevention and Treatment of Chemotherapy-Induced Peripheral Neuropathy: A Mechanism- and Screening-Based Strategy - Yamamoto, Shota; Egashira, Nobuaki (Frontiers in Pharmacology, 2021)
Chemotherapy-induced peripheral neuropathy (CIPN) is a severe adverse effect observed in most patients treated with neurotoxic anti-cancer drugs. Currently, there are no therapeutic options available for the prevention of CIPN. Furthermore, few drugs are recommended for the treatment of existing neuropathies because the mechanisms of CIPN remain unclear. Each chemotherapeutic drug induces neuropathy by distinct mechanisms, and thus we need to understand the characteristics of CIPN specific to individual drugs. Here, we review the known pathogenic mechanisms of oxaliplatin- and paclitaxel-induced CIPN, highlighting recent findings. Cancer chemotherapy is performed in a planned manner; therefore, preventive strategies can be planned for CIPN. Drug repositioning studies, which identify the unexpected actions of already approved drugs, have increased in recent years. We have also focused on drug repositioning studies, especially for prevention, because they should be rapidly translated to patients suffering from CIPN.